Estimation of Vertical Distance and Reduce Level using Modern Mine Survey Equipments (Total Station) at Sub Level in Maddhapara Granite Mine, Bangladesh - Md. Minhaj Uddin Monir (Institute of Advanced Engineering and Science, 2014)
An underground mine survey work is done using Total Station (TS) at sub-level from third drilling drift to cage shaft in Madhyapara Granite Mine (MGM). The MGM is situated at Madhyapara in Dinajpur district, NW Bangladesh. Room and pillar sub-level stoping underground mining method is applied in MGM and extracted economic mineral (granite, granodiorite, diorite etc) from five stopes, three in the northern side and two in the southern side. Different types of survey equipments (measuring tape, normal staff, compass, ranging rod, automatic level, automatic theodolite) were used in MGM during the development period for the constructions of shafts, underground roadways, drilling drifts, sumps, loading bunkers, cross cuts, stopes etc. MGM contains two vertical shaft (Cage Shaft and Skip Shaft) and three underground levels, ventilation level is used for mine air ventilation, sub-level is for drilling or blasting and production level is for production of mineral ores. The dimension of each stope (l×h×w) is 276,000 m3 (230 m × 60 m × 20 m) as per design. Modern surveying in MGM reduce the error survey data which were used to develop the further constructions as per design and also monitor the weak zones or mine subsidence rate to minimize mine accidents. During the year of 2008-2009, an underground mine survey work is done and calculate the Reduce Level (RL) at various points. The first R.L in the mouth of third drilling drift is -247.267 m and last RL near the cage shaft is -246 m. The vertical distance is also calculated with taping method from surface (mean sea level) to ventilation level, sub level and production level is -228 m, -246 m and -270 m respectively. Using TS and other modern survey accessories regularly in MGM may give the actual survey results which may monitor all the mine constructions and find out the weak zones (if detect) and recommends for supporting system as per geotechnical pressures and finally MGM get read of any type of mine accidents and successfully continue as the mine life time.